Harmonizing art education in empowering youth women in tertiary institutions on the light of development goal in Mwanza, Tanzania - Mkulu , Demetria Gerold (Global Journal of Social Sciences Studies, 2025)
Tertiary learning institutions play a critical role in building professional capability that is instrumental towards realization of goal number four of agenda 2030. The following research questions were formulated to give answers to the research problem: What factors inhibit girls’ involvement in advanced learning in Mwanza, Tanzania? What strategies tertiary institutions employ to empower young women? How can the issue of young women in university be addressed? The study adopted mixed research approach while explanatory research design was adopted in qualitative phenomenology. The total number of respondents was 250. The researcher employed questionnaires, in-depth interview guide and personal observation. The instruments were validated and reliabilities were 0.89 correlation coefficient. Qualitative instruments trustworthiness was checked. Quantitative data was analyzed by Statistical Package for Social Science (SPSS) version 22. The results demonstrated that tertiary institution empowers the young women, to become competent leaders, manage their lives, become shining stars in the country and the world. However, there are relatively more females enrolled in primary and secondary schools while a few are in tertiary institutions. Nevertheless, the educational gap between female and male youth is still very wide with women far behind, shortage of qualified women for various posts. The research suggested that tertiary institutions build human capital. Negative attitude towards female education should be discouraged through mass media. Early marriage culture should be banned and special programme of scholarships should be lunched for female. The government should introduce various programmes including STEM to empower youth women in achieving the national development goal.